Space of Cross-Disciplinary Researches of Life, Nature and Society - Paranina Alina (Journal of Biosemiotic Research, 2018)
Journal of Biosemiotic Research is a new periodical devoted to a young, actively developing science. A review of recent scientific publications shows that in the broad scientific space of biosemiotics contemporary questions and
Keywords: Biosemiotc